Mechanisms underlying fat-induced hepatic insulin resistance. (October 2007) - Park, Edward; Giacca, Adria
Free fatty acids (FFAs), which are often elevated in obesity, cause insulin resistance. While the effects of FFAs on muscle glucose metabolism are well known, the mechanisms by which FFAs cause hepatic insulin resistance are incompletely understood. Recent evidence points to an accumulation of fat metabolites that activates various serine/threonine kinases, such as protein kinase C, c-Jun NH2 -terminal kinase 1 and IκκBαα kinase, as a key event in the pathway of fat-induced hepatic insulin resistance. In this review, we present recent progress regarding the potential causal mediators of fat-induced hepatic insulin resistance and discuss the possible pathways by which they interact to induce impairment of hepatic insulin signaling.